Key technology to non-aqueous and multi-step biocatalysis: Pickering emulsions - Ansorge-Schumacher, Marion B.; Plikat, Christoph (Frontiers in Catalysis, 2022)
Considering the importance of biocatalysis in chemical synthesis, technologies allowing full exploitation of its potential are urgently wanted. Eleven years ago, our team proposed Pickering emulsions as a concept to overcome the severe restrictions set by the general requirement for the presence of water. In this brief perspective, we demonstrate that the insights into bioactive Pickering emulsions gathered meanwhile strongly designate it a key technology to non-aqueous and multi-step biocatalysis. Mainly, this relates to the extensive compatibility of this system with different solvents, materials, biocatalysts, reactions and demands on productive use. We here give a brief overview of the most relevant details, including recent results from our own research.